Review of David Levin. 2007. Unsettling Opera: Staging Mozart, Verdi, Wagner, and Zemlinsky. Chicago and London: University of Chicago Press - Casadei, Delia (Current Musicology, 2009)
David Levin’s Unsettling Opera: Staging Mozart, Verdi, Wagner, and Zemlinsky is an ambitious book, and one that opens with an unusual insight: namely, that the onstage performance practice of opera in the last twenty years is a field ripe for academic discourse, one that promises to uncover new perspectives on the restricted repertoire of historical musicology. Levin suggests that operatic productions in Europe and the United States have amply paid homage to academic concerns about the production of meaning and other post-modern enthusiasms. Yet academia has not returned the favor, instead preferring studies of historical performance practice that largely ignore contemporary productions. Of course, it is by no means the case that no one cares about these new productions. Levin spends a good part of his preface quoting the Financial Times’s and the New York Times’s dismissals of two provocative productions of Don Carlos and Die Entfuhrung aus dem Serail. Indeed, Levin may even have taken his cue for this book from the sheer volume of critical bile elicited by the work of directors such as Hans Neuenfels or Peter Sellars; he knows full well that a reception marked by anger and rash dismissal is the signpost to an interesting field of inquiry.